PENGARUH JUMLAH MATA TUNAS BATANG ATAS DAN TINGGI BATANG BAWAH PADA SAMBUNG PUCUK TERHADAP PERSENTASE TUMBUH JAMBU AIR (Syzygium Samarangense) - Supriyono Supriyono; Tarwa Mustopa; Nunuk Helilusiatiningsih; Fristama Maulana (Universitas Muhammadiyah Mataram, 2020)
Water guava (Syzygium Samarangense) was a popular plant in Indonesia because it was fresh and sweet. The aim of this research was to analyze the effect of the number of shoots of the upper stems and height of the rootstock at the shoot graft on the percentage of growing water guava. The method used in this study was a completely randomized design, factor into one rootstock length, namely 10 cm, 15 cm, and 20 cm. and the second factor was the number of buds on the scion, namely 2, 3, and 4. The results showed that there was a significant interaction in the treatment combination of the number of 4 buds on the upper stem and the length of the rootstock 15 cm at 35 days after grafting affected the growth percentage and growth in the number of leaves and length of the scion.